‘Hazardous on My Soul’: (Dis)compassion and Emotive Dissonance in Prison Work - Higgins, Ethan M. (The British journal of criminology, 2024)
A history of social research has aimed to illuminate consequences for the psyche of workers that carry out occupations in dehumanizing contexts. In criminology, scholarship has detailed concern over how carceral contexts produce detriment via emotional labour for workers. Although prison work has been shown to necessitate emotional suppression, studies also find workers can bear intimacy for the incarcerated. We contribute to the prison scholarship by illustrating these emotive paradoxes that represent dissonance for staff. We draw from 18 focus groups of staff, to examine how emotive dissonance manifests from contradictory feeling rules in prison work. We explore emotive disharmony among the workgroup that comes from opposing feeling rules, and, we explore how workers experience with emotive dissonance manifests as emotional estrangement. Our findings help contemplate the implications of navigating emotion within dehumanizing contexts and illustrate that how staff treat the incarcerated has implications for their own sense of humanity.